PENGARUH PEMBERIAN KOMBINASI SEL PUNCA PULPA GIGI DAN RECOMBINANT HUMAN BONE MORPHOGENETIC PROTEIN-2 TERHADAP KADAR FOSFATASE ALKALI PADA PULPA GIGI TIKUS TERINFLAMASI: COMBINATION OF RECOMBINANT HUMAN BONE MORPHOGENETIC PROTEIN- 2 AND DENTAL PULP STEM CELLS ENHANCED EXPESSION OF ALKALINE PHOSPHATASE ON INFLAMED RAT’S PULP - Endang W Bachtiar; Mindya Yuniastuty; Aimee Monica; Boy M Bachtiar (TALENTA, 2011)
Pulp irritation will form reparative dentin as a defense mechanism. Currently, the materials used to help the defense pulp still have many shortcomings. Therefore, the effect of dental pulp stem cells (DPSC) and rhBMP- 2 combination on alkaline phosphatase (ALP) expresion in rat ’s dental pulp was analyzed in this research. Lipopolysaccharide was used to irritate the pulp of 12 Sprague-Dawley rats. Materials were then applied to each group and ALP expression was performed on the first and second week. The result showed that in the first week, giving a combination of pulp stem cells with recombinant BMP-2 had not been visible to increase expression of alkaline phosphatase (ALP), a biomarker regeneration of pulp, but the increase in ALP expression occurred in the second week. In conclusion, a combination of pulp stem cells and rhBMP-2 can increase the expression of ALP on inflamed rat’s pulp.